Effects of Demand Fluctuation and Mitigation Strategy in Low Voltage EV Charging Station by Battery Energy Storage System - Nirudh Jirasuwankul; Sakon Klongboonjit; Chalermchat Manop (International Review of Electrical Engineering (IREE), 2021)
In this paper, the effects of fluctuating demand on a low voltage electric utility system equipped with electric vehicular charging station have been studied and mitigation strategy has been proposed. By applying Battery Energy Storage System (BESS) and demand management (DMM), the stored electric energy during an off-peak period is controlled to supply the spiky demand during the EV charging period. Employing different approaches of discharging control, the BESS can response and shape the peaky demand into the smoothed one with an elevated load factor. Therefore, the result is that energy cost of EV charging has been reduced by cutting the demand charge during the on-peak period and the power quality of the system has also been improved. These findings are confirmed and illustrated by simulation results.
Keywords: Electric Vehicles and Infrastructure; Advanced Battery Technologies Research; Smart Grid Energy Management